Evaluation of Pain in Relation to Root Canal Treated Teeth Having Instrument Separation-A Retrospective Analysis - Nur Qistina Binti Ahmad Fauzi1 , Raghu Sandhya2 , Gurunathan Deepa3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
One of the most common mishaps during root canal treatments is the separation of an endodontic instrumentduring cleaning and shaping. The main problem to this is the improper debridement of the apical portionof canal and directly compromises the success of the treatment. The aim of this study was to evaluate theassociation of pain in root canal treated teeth having instrument separation. A total of 29 patients whohave undergone root canal treatment and reported with a separated instrument were evaluated. Each of thepatient’s age, gender, tooth number, the association of pain, nature and the duration of pain was obtainedfrom the patient records of the institution from June 2019 to March 2020. In this study, out of the totalsample size, 15 (51.7%) of patients were females while the remaining 14 (48.3%) patients were males. It wasshown that 72.4% of the patients did not experience pain with the presence of instrument separation in theirroot canal treated teeth, while 29.6% experienced pain. Position of the tooth in the arch did not influencethe experience of pain among the patients (Chi - Square test, P- 0.35, >0.05). Within the limits of the study,an association between pain and root canal treated teeth with instrument separation was not established.Though gender and tooth did not influence the experience of pain, many female patients in the present studyexperienced pain. The pain was more often associated with lower posteriors.